Non Descent Vaginal Hysterectomy: A Rational Surgical Approach (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): The aim of the study wasto evaluate the safety and feasibility of non-descent vaginal hysterectomy in advancing gynaecological practice.Materials and methods: This prospective observational study was conducted from 1st July 2013 to 31st June 2014 in Obstetrics and Gynaecology Department of Kumudini Womens Medical College & Hospital, Mirzapur, Tangail. Fifty patients who needed hysterectomy for benign gynaecological disorders and who had no descent of uterus or vagina were the target population for this study. Main outcome measures were i) difficulty of operation, ii) procedures for overcoming the difficulties,iii) switch over to abdominal route, iv) time taken to complete the operation, v) blood loss during operation vi) need of blood transfusion and vii) postsurgical hospital stay.Results: In all (100%) cases vaginal hysterectomy was completed successfully. Commonest age group (46%) was between 41-45 years. All patients were parous. Size of the uterus was less then 8 wks in 21 cases, 8wks to 12 wks in 27 cases and more than 12 wks in 02 cases. Commonest indication was dysfunctional uterine bleeding (DUB) (44%). Mean duration of surgery was 50.5 ± 5.46 minutes. Mean blood loss was 100± 22.43 ml.Blood transfusion was required in four cases. Average duration of hospital stay was 3.1± 1.2 days. Complications were minimum which included, bladder injury, UTI and Vault infection.Conclusions: In properly selected cases non-descent vaginal hysterectomy is safe, feasible and patient friendly.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 15-19